Prevalence of Subclinical Mastitis and Associated Bacterial Pathogens in Milkshed Districts of Odisha, India - Sarangi, Swetapadma; Sahoo, Niranjana; Biswal, Sangram; Pahari, Avishek; Sardar, Kautuk K.; Das, Bhabesh C. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study deals with subclinical mastitis (SCM) with respect to prevalence, etiology and antibiogram pattern. A total of 1273cross-bred Jersey lactating cows in four milkshed districts of Odisha viz. Jagatsinghpur, Puri, Khordha and Cuttack were screenedthrough modified california mastitis test during the period from September 2019 to January 2020. Overall 57.58% prevalence ofSCM was recorded. Microbiological examination of 72 milk samples positive for SCM revealed association of Staphylococcus aureus inmaximum (65.27%) cases followed by Streptococcus uberis (9.7%), Streptococcus agalactiae (8.3%), Pseudomonas aeruginosa (5.55%) and Escherichia coli (2.76%). In vitro antibiotic sensitivity test results indicated > 95 % S. aureus isolates were quite sensitive to the antibiotics like gentamicin, ceftizoxime, cefuroxime and ceftiofur.
Keywords: : Antibiotic Sensitivity Test, Cross-bred Jersey cows, Prevalence; Subclinical Mastitis